ECOCRITICAL AESTHETICS IN VISUAL AND PERFORMING ARTS: INTERPRETING ENVIRONMENTAL CONSCIOUSNESS THROUGH CREATIVE EXPRESSION - Chhotray, Manisha; Nayak, Suresh Chandra; Chhotroy, Nibedita; Dey, Meenakshi; Doley, Jyoti; Hazarika, Jintu; Kiran, Swati (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The escalating ecological crisis of the Anthropocene has required interdisciplinary perspectives on knowledge and dissemination of environmental issues, and the arts are becoming an important source of engagement. This paper investigates ecocritical aesthetics in the visual arts and performing arts with a particular emphasis on how the creative expression interprets and communicates environmental awareness. This study was based on the ecocritical and interpretive paradigm, where the qualitative and comparative approach was followed on the basis of secondary information on ecological art, design, and performance. The discussion covered the thematic representations, aesthetic strategies and embodied expression in visual and performing fields. The results found that the symbolism, materiality, and compositional methods are used most often in visual arts to depict the environmental concerns, whereas the performing arts depend on the movement, spatial, and affective means in order to tell ecological stories. It was discovered that the inclusion of ecological themes in artistic activities led to a greater awareness of audiences, emotional reaction to and cognitive interest in environmental concerns. The paper emphasizes the symbiotic aspects of visual and performing arts in creating environmentally aware and sustainability-related discussions. The research highlights the transformative nature of the artistic practice by bringing together it with the ecological consciousness of creative expression in solving modern environmental issues.